Automation in Recruitment: A New Frontier. Issue 2 (November 2018) - Gupta, Pooja; Fernandes, Semila F.; Jain, Manish
The case is about the urge for improving the processes and utilizing technologies available in market for Human Resource Management Services especially in recruitment. The dilemma in the case is whether the company should opt for automation or not. And if the company is adopting automation to support workforce planning and recruitment functions, is the company ready for the same. The HR industry at large is aware of the challenges faced by the recruitment teams in terms of the various hiring functions involving sales engine, sourcing, interviewing, providing offers, post offer follow-ups and finally joining and induction. To address this challenge, the case touches on instituting a culture change by embracing technology into divisions which are not yet open to adopting innovative methods. The company is looking at incorporating Artificial Intelligence in its various processes. It is also looking at Robot Process Automation to perform standard HR functions in the recruitment process. The company must decide whether to implement automation and if it does, how it should be executed. The case also debates on whether technology would increase the effectiveness of talent acquisition function and bring a change in the administrative HR image or would this automation-led hiring take away the control from the company human resources?